A clickable glutathione approach for identification of protein glutathionylation in response to glucose metabolism. Issue 8 (24th May 2016) - Samarasinghe, Kusal T. G.; Munkanatta Godage, Dhanushka N. P.; Zhou, Yani; Ndombera, Fidelis T.; Weerapana, Eranthie; Ahn, Young-Hoon
Abstract : Clickable glutathione was used for analyzing the reversible change of protein glutathionylation in response to glucose metabolism and mitochondrial ROS. Abstract : Glucose metabolism and mitochondrial function are closely interconnected with cellular redox-homeostasis. Although glucose starvation, which mimics ischemic conditions or insufficient vascularization, is known to perturb redox-homeostasis, global and individual protein glutathionylation in response to glucose metabolism or mitochondrial activity remains largely unknown. In this report, we use our clickable glutathione approach, which forms clickable glutathione (azido-glutathione) by using a mutant of glutathione synthetase (GS M4), for detection and identification of protein glutathionylation in response to glucose starvation. We found that protein glutathionylation is readily induced in HEK293 cells in response to low glucose concentrations when mitochondrial reactive oxygen species (ROS) are elevated in cells, and glucose is the major determinant for inducing reversible glutathionylation. Proteomic and biochemical analysis identified over 1300 proteins, including SMYD2, PP2Cα, and catalase. We further showed that PP2Cα is glutathionylated at C314 in a C-terminal domain, and PP2Cα C314 glutathionylation disrupts the interaction with mGluR3, an important glutamate receptor associated with synaptic plasticity.